Effects of maturity level, steam treatment, or active packaging to maintain the quality of minimally processed mango (Mangifera indica cv. José). Issue 7 (17th May 2021) - Leneveu‐Jenvrin, Charlène; Apicella, Annalisa; Bradley, Kelly; Meile, Jean‐Christophe; Chillet, Marc; Scarfato, Paola; Incarnato, Loredana; Remize, Fabienne
Abstract: The shelf‐life of minimally processed José mango is primarily limited by browning during refrigerated storage. Three approaches were assayed to increase product shelf‐life. Processing fruit sampled at an earlier ripening stage reduced browning during storage but fruit remained acidic. Steam treatment at 60°C for 3 min reduced polyphenol oxidase activity by 72%, and microbial population remained below 2.5 log CFU/g after 10 days of storage. However, the visual aspect of steam‐treated mango pieces turned to dully green. Lastly, different multilayer film configurations containing an oxygen scavenger were tested. Two films, having a thickness of the active layer of 40 µm, limited color change by 32%–36% and hardness decrease of mango cuts after 7 days of storage at 4°C. Both active and passive layers of films contribute to maintain fruit quality. The use of active packaging was promising but requires further examination and possibly combination with other physical or chemical treatments. Novelty impact statement: A short steam treatment partly inactivates PPO and increases microbiological quality but failed to maintain fruit color during storage. On the opposite, active packaging with oxygen scavenger limits browning and hardness loss during storage. Active and passive layers of films both play a role in maintaining fruit quality.